Effectiveness and Safety of Adalimumab Biosimilar SB5 in Inflammatory Bowel Disease: Outcomes in Originator to SB5 Switch, Double Biosimilar Switch and Bio-Naïve SB5 Observational Cohorts. (5th June 2021) - Derikx, Lauranne A A P; Dolby, Heather W; Plevris, Nikolas; Lucaciu, Laura; Rees, Caitlin S; Lyons, Mathew; Siakavellas, Spyros I; Constantine-Cooke, Nathan; Jenkinson, Philip; Su, Shanna; O'Hare, Claire; Kirckpatrick, Laura; et al.
Abstract: Background and Aims: Multiple adalimumab [ADA] biosimilars are now approved for use in inflammatory bowel disease [IBD]; however, effectiveness and safety data remain scarce. We aimed to investigate long-term outcomes of the ADA biosimilar SB5 in IBD patients following a switch from the ADA originator [SB5-switch cohort] or after start of SB5 [SB5-start cohort]. Methods: We performed an observational cohort study in a tertiary IBD referral centre. All IBD patients treated with Humira underwent an elective switch to SB5. We identified all these patients in a biological prescription database that prospectively registered all ADA start and stop dates including brand names. Data on IBD phenotype, C-reactive protein [CRP], drug persistence, ADA drug and antibody levels, and faecal calprotectin were collected. Results: In total, 481 patients were treated with SB5, 256 in the SB5-switch cohort (median follow-up: 13.7 months [IQR 8.6–15.2]) and 225 in the SB5-start cohort [median follow-up: 8.3 months [4.2–12.8]). Of the SB5-switch cohort, 70.8% remained on SB5 beyond 1 year; 90/256 discontinued SB5, mainly due to adverse events [46/90] or secondary loss of response [37/90]. In the SB5-start cohort, 81/225 discontinued SB5, resulting in SB5-drug persistence of 60.3% beyond 1 year. No differences in clinical remission [ p = 0.53], CRP [ p = 0.80], faecal calprotectin [ p = 0.40] and ADA trough levels [ p = 0.55] were found between baseline, week 26 and week 52 following switch. Injection site pain was the most frequently reported adverse event. Conclusion: Switching from ADA originator to SB5 appeared effective and safe in this study with over 12 months of follow-up.